Methotrexate use in allergic contact dermatitis: a retrospective study. (6th December 2017) - Patel, Ashaki; Burns, Erin; Burkemper, Nicole M.
Summary: Background: Methotrexate, a folate antimetabolite, is used to treat atopic dermatitis and psoriasis. Although methotrexate's therapeutic efficacy has been noted in the literature, there are few data on the efficacy of methotrexate treatment for allergic contact dermatitis. Objective: To evaluate the efficacy and tolerability of methotrexate in treating allergic contact dermatitis at a single institution, and also to assess methotrexate efficacy in patients with chronic, unavoidable allergen exposure. Methods: We performed a retrospective chart review of 32 patients diagnosed with allergic contact dermatitis by positive patch test reactions, and who received treatment with methotrexate from November 2010 to November 2014. Demographic and treatment‐associated data were collected from electronic medical records. Ten patients were identified as allergen non‐avoiders secondary to their occupation, and were subgrouped as such. Results: Seventy‐eight per cent (25/32) of patients showed either a partial or a complete response. Methotrexate had a comparable efficacy rate in the allergen non‐avoiders subset, at 10 of 10. Of the 32 patients, 23% (5/22) had complete clearance of their dermatitis, and 1/10 of allergen non‐avoiders had complete clearance of their dermatitis. Conclusion: Methotrexate is a well‐tolerated and effective treatment for allergic contact dermatitis, and shows comparable efficacy to immunomodulatory agents such as cyclosporine and azathioprine, with robust efficacy despite persistent allergen exposure in patients with allergic contact dermatitis.